ANALISIS MIMETIK TERHADAP NILAI SOSIAL PADA KUMPULAN CERPEN KEJAR IMPIAN KALA PANDEMI KARYA OKTAVIANTI SEBAGAI ALTERNATIF BAHAN AJAR SASTRA SISWA SMA KELAS XI - Ima Rismawati; Panca Pertiwi Hidayati; Yeni Cania Puspita (STKIP Subang, 2022)
This study aims to find social value in the collection of short stories Kejar Impian Kala Pandemi by analyzing it and utilizing the results of the analysis as an alternative teaching material for class XI high school students. This study uses descriptive qualitative research methods. Based on the results of the analysis, it shows that religious social values, kinship, mutual cooperation, caring for others, never giving up, being loyal and patient are studied using a mimetic approach. The mimetic approach means imitation in real life in the form of literary works, namely short stories. The number of social values contained in the short story collection Kejar Impian Kala Pandemi by Oktavianti is 63. The teaching materials made by the author are in the form of LKPD. The author hopes that this LKPD can help students and students in the teaching and learning process, especially in Indonesian subjects, especially short story material.